The Dutch Disease: An Overview - Zuzana Brinčíková (European Scientific Journal, ESJ, 2016)
The Dutch disease is a negative impact of the increase in foreign income on the economic development that often affects relatively small resource-rich countries. The consequent appreciation of the real exchange rate could harm the export competitiveness of inflows receiving countries and thus lower their growth potential. It could affect the macroeconomic stability, the competitiveness of the export sector and the external sustainability of the countries as it diverts country´s resources away from activities that are more contribute to growth in a long run. Paper presents an introduction to the phenomenon of the Dutch disease and the current state of the theoretical and practical aspects of this problem.